ANALISIS HUKUM TERHADAP PUTUSAN NOMOR 5056/Pdt.G/2019/PA.Clp TENTANG ISBAT NIKAH POLIGAMI LIAR - Haryono, Masadi; Bahar, Mukhlis; Azwar, Zainal (Fakultas Syariah (Syari'ah Faculty ), 2025)
This article analyses Cilacap Religious Court Decision Number 5056/Pdt.G/2019/PA.Clp regarding isbat nikah for illegal polygamy. This research aims to identify the basis of legal considerations used by the panel of judges in deciding the case and the implications of this decision on the legal status of marriage and children. the legal status of the marriage and the children resulting from the marriage. marriage. The method used is a normative juridical approach with qualitative analysis, referring to laws and regulations. qualitative analysis, referring to legislation and principles of Islamic law. The results showed that the panel of judges granted the application for isbat nikah on the grounds that the polygamous marriage had met the legal requirements according to Islamic law and for the sake of has fulfilled the legal requirements according to Islamic law and for the benefit and protection of children's nasab. protection of children's nasab. However, this decision also raises questions regarding compliance with the provisions of SEMA No. 3/2018 which regulates polygamy without court permission. on polygamy without court permission. As such, this article provides insight into the dynamics of family law in the context of polygamy in Indonesia and the importance of enforcing legal provisions to protect the rights of all parties involved.